2019
DOI: 10.3389/fimmu.2019.02872
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling and Its Significance Within the Tumor Microenvironment: Novel Therapeutic Insights

Abstract: Wnt signaling is one of the central mechanisms regulating tissue morphogenesis during embryogenesis and repair. The pivot of this signaling cascade is the Wnt ligand, which binds to receptors belonging to the Frizzled family or the ROR1/ROR2 and RYK family. This interaction governs the downstream signaling cascade (canonical/non-canonical), ultimately extending its effect on the cellular cytoskeleton, transcriptional control of proliferation and differentiation, and organelle dynamics. Anomalous Wnt signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 125 publications
2
170
0
7
Order By: Relevance
“…In this study, we have demonstrated that anti-IL-3R-EVs also reduce β-catenin expression in tumor-bearing mice, suggesting that anti-IL-3R-EVs are also able to target the canonical wingless Wnt/β-catenin pathway in neoplastic cells. β-catenin accumulation and the acquisition of mesenchymal markers, as Vimentin, in tumor cells, are associated with cancer cells’ ability to spread to distant sites 48 50 . Indeed, anti-IL-3R-EVs were found effective in reducing the expression of Vimentin, and animals treated with anti-IL-3R-EVs were almost protected from the occurrence of liver and lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have demonstrated that anti-IL-3R-EVs also reduce β-catenin expression in tumor-bearing mice, suggesting that anti-IL-3R-EVs are also able to target the canonical wingless Wnt/β-catenin pathway in neoplastic cells. β-catenin accumulation and the acquisition of mesenchymal markers, as Vimentin, in tumor cells, are associated with cancer cells’ ability to spread to distant sites 48 50 . Indeed, anti-IL-3R-EVs were found effective in reducing the expression of Vimentin, and animals treated with anti-IL-3R-EVs were almost protected from the occurrence of liver and lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A second example of trafficking control through cargo PTMs is provided by Sun et al (2017) in their study of Wnts ( Figure 5B ). Wnts are an important class of cell surface receptors that are required for embryonic development in animals and are dysregulated in human cancers ( Steinhart and Angers, 2018 ; Patel et al, 2019 ). Wnt secretion requires the transmembrane protein Wntless, which binds Wnts directly, but the mechanisms controlling Wnt/Wntless vesicle assembly and trafficking are incompletely understood.…”
Section: Cargoes Cargo Receptors and Accessory Proteinsmentioning
confidence: 99%
“…In addition, Wnt signaling also plays an important role in the regulation of tumor immune microenvironment, which can regulate the in ltration and activity of various types of T cells in tumors. Usually excessive activation of Wnt signaling pathway in tumors can lead to tumor immunosuppression and immune escape [49,50]. In colorectal cancer, inhibiting the activation of the Wnt signaling pathway can reduce the in ltration of Treg cells in the tumor and up-regulate the content of CD8 + T cells in the tumor, thereby enhancing the response to immunotherapy [51].…”
Section: Discussionmentioning
confidence: 99%